But you look so normal : lost and found in a hearing world - Marseille, Claudia (She Writes Press, 2024)
When four-year-old Claudia Marseille was diagnosed with severe hearing loss and received her first hearing aid, her lifelong journey to fit in began. Here, she reveals how she overcame loneliness and isolation and carved out a fulfilling life for herself somewhere between the mainstream culture and the Deaf world." --